A pharmacovigilance system for treatment access and medical donation programs: The Max Foundation experience - Ann Kim Novakowski; Pat Garcia-Gonzalez; Michael Wrigglesworth; Andy Stergachis (BMC, 2018)
Abstract Background Cancer is a major burden of disease in low- and middle-income countries (LMICs) yet financial barriers limit access to life-saving oncology drugs. Medical donation and other drug access programs can help improve patient access to essential medicines, such as quality assured oncology drugs in LMICs. However, there are no published examples of the conduct of pharmacovigilance with donated medical products intended for use in LMICs where pharmacovigilance is weak. We describe a partnership between a pharmaceutical company and a non-governmental organization as a case example that addresses the challenges in performing pharmacovigilance with donated medicines in LMICs. The Max Foundation's direct to patient model is designed to improve global access to quality assured oncology drugs through access programs such as the Glivec® (generic name: imatinib) International Patient Assistance Program (GIPAP). Results Between 2013 and 2016, in the course of managing the GIPAP program, The Max Foundation was made aware of 13,039 instances of adverse events (AEs). These AEs were reported to The Max Foundation by physicians, patients, and caregivers. The Max Foundation reported these AEs to Novartis through the AE reporting tool within its Patient Assistance Tracking System (PATS). Physicians were the reporters for 58% of the AEs while the remainder of the AEs were reported directly by patients or caregivers. The overall rate of reported AEs remained relatively steady for the years 2013 through 2016 at 92, 95, 86, and 97 AEs reported per 1000 persons who received Glivec® per year, respectively. The vast majority of adverse events (85%) were reported from countries where The Max Foundation has a MaxStation, i.e., where The Max Foundation staff interact directly with physicians and patients at clinics or over the phone. AE reporting rates were consistently higher in all years studied from countries where The Max Foundation has a MaxStation. While India accounted for the largest number of reported adverse events in 2016 (1990), Bolivia had the highest rate of reported adverse events at 484 AEs per 1000 patients. Conclusions International patient assistance programs that provide access to medicines can have an important role in assisting pharmaceutical companies in fulfilling their pharmacovigilance obligations. Adverse event information collected through PATS can potentially contribute to the overall body of knowledge on the safety of medicinal products.